Opportunity-related behaviors in international entrepreneurship research: a multilevel analysis of antecedents, processes, and outcomes (2020)
The opportunity has become a central concept in International Entrepreneurship (IE) literature, and there is now a critical mass of literature focused on entrepreneurial behaviors of pursuing opportunities across national borders. However, scholars claim that research on these opportunity-related behaviors should consider a multilevel analysis where the interaction between the contexts, entrepreneurial action, and the opportunities can be clarified. From a multilevel analysis, the present study aims to understand antecedents, processes, and outcomes of opportunity-driven behaviors in the IE field. By conducting a systematic literature review, we analyze studies over the last 30 years (1989 2019). We found that the IE research around opportunities and related behaviors, far from suffering paucity and a weak conceptual basis, is abundant and is broadening its territory and boundaries. This study makes four contributions. First, we extend opportunity-related research in IE literature by considering a multilevel approach that incorporates individual, firm, and environmental aspects. Second, we offer an integrative model that outlines the antecedents, processes, and outcomes of opportunity-driven behaviors. Third, we suggest a definition of the IE field and the opportunity concept that can enrich the international opportunity debate, as well as its theoretical discussion. Fourth, we present theoretical contributions by identifying past advances and directions for future research. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.